Study on heat transfer process of microwave flash evaporation using water as medium. (February 2021) - Tian, Shihong; Gu, Yongwan; Ju, Shaohua; Xu, Lei; Zhang, Libo; Zhang, Lihua; YuWen, Chao
Highlights: A microwave flash evaporation system (MFE) is demonstrated. MFE process is more efficient than CFE process. Microwave heating raises liquid temperature and intensifies heat transfer during MFE. Dimensionless analysis is used in heat transfer characterization of MFE process. Heat transfer intensity increases with superheating degree in MFE process. Abstract: The evaporation efficiency of conventional flash evaporation was limited by the superheated degree of liquid, process intensification was one profitable method to enhance evaporation efficiency of flash evaporation. In this article, microwave was used as external energy field to enhance flash evaporation process, the proprietary equipment was developed to validate the performance of microwave flash evaporation (MFE) process, and series experiments were carried out under the conditions of the microwave power varied from 0.81 to 1.35 kW, liquid flow rate from 10 to 40 L/h and initial pressure from 4.0 to 8.0 kPa. Results indicated the productivity of microwave flash evaporation (MFE) was more than conventional flash evaporation (CFE) due to the heating effect of microwave. The temperature of flash evaporation chamber was among 19 to 50 °C and pressure of flash chamber during experiment was among 4 to 12 kPa, according to the variation of temperature and pressure of flash evaporation chamber, the flash evaporation was divided into two stage, i.e., rapid flash evaporation stage and equal flash evaporation stage. The dimensionless numbers of non-equilibrium fraction (NEF) and Jakob number ( Ja ) was applied to assess the heat transfer process, further analysis indicated the variation of NEF and Ja for MFE was influenced by flow rate, superheating degree and microwave power, and the Ja increased with the increase of superheating degree. This mechanism of microwave enhancing flash evaporation process was inferred as microwave fed into vessel in situ to replenish thermal loss of liquid and be absorbed to induce temperature raise instantaneously, which led to the transient flash evaporation or direct boiling evaporation of liquid.